Influence of aluminosilsesquioxane on epoxy resin curing process - Matykiewicz, D.; Dudziec, B.; Sterzyński, T. (Polimery, 2014)
The curing process of epoxy resin Epidian 6 with bis(heptaisooctylaluminosilsesquioxane) (AlPOSS) was investigated. Curing kinetics of the composition was studied with differential scanning calorimetry (DSC) at different heating rates. Activation energy (Ea) was calculated based on Kissinger method. Fourier transform infrared (FT-IR) spectroscopy was used to monitor the development of curing process and chemical changes in the epoxy matrix. The research results indicated that AlPOSS may be used as a curing agent for epoxy resins.